KAJIAN LITERATUR: PENGARUH TELENURSING TERHADAP KUALITAS HIDUP PASIEN DENGAN PENYAKIT GINJAL KRONIK YANG MENJALANI CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD) [LITERATURE REVIEW: THE EFFECT OF TELENURSING ON THE QUALITY OF LIFE OF PATIENTS WITH CHRONIC KIDNEY DISEASE UNDERGOING CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD)] - Ballsy Cicilia Albertina Pangkey; Fendy Yesayas; Fatima Ura Pabane (Universitas Pelita Harapan, 2021)
Chronic Kidney Disease (CKD) is one of the diseases associated with symptoms or disability that requires long-term management. One of the interventions that can be done in patients with CKD is Continuous Ambulatory Peritoneal Dialysis (CAPD). Self-care for patients with CKD requires optimal services for medical, social, mental, and emotional problems. Telenursing can be used as a process of providing management, coordination of care, and health services through information technology and telecommunications, so that patients’ problem related to treatment can be resolved and the quality of life of patients can be improved. The purpose of this study was to determine the effect of telenursing on the quality of life of patients with CKD undergoing CAPD. PICOT framework was utilized to find related journals. The data sources of this researchwere taken from the e-resources database of National Library of Indonesia, PubMed and Google Scholar and then selected using the PRISMA flow diagram to produce nine articles. Each article had been described and criticized in the form of a matrix table using a simplified approach method. Three themes then emerged from the analysis, namely the quality of life of CKD patients who were running CAPD was good, the quality of life of CKD patients who were running CAPD was better than patients who were undergoing hemodialysis, and the quality of life of CKD patients who were running CAPD by telenursing had increased. Telenursing can facilitate patient access in seeking health services and increase the effectiveness of patient time, so that the patient's quality of life can improve.BAHASA INDONESIA ABSTRAK: Penyakit Ginjal Kronik (PGK) merupakan salah satu penyakit yang berkaitan dengan gejala-gejala atau kecacatan yang membutuhkan penatalaksanaan jangka panjang. Salah satu intervensi yang dapat dilakukan pada pasien dengan PGK adalah Continuous Ambulatory Peritoneal Dialysis (CAPD). Perawatan diri pada penderita PGK membutuhkan layanan yang optimal terhadap masalah-masalah yang bersifat medis, sosial, mental, dan emosional. Telenursing dapat dijadikan sebagai suatu proses pemberian manajemen, koordinasi asuhan, dan layanan kesehatan melalui teknologi informasi dan telekomunikasi, sehingga masalah-masalah yang ada pada pasien terkait pengobatan dapat teratasi dan kualitas hidup pasien dapat meningkat. Tujuan penelitian ini untuk mengetahui pengaruh telenursing terhadap kualitas hidup pasien dengan PGK yang menjalani CAPD. Dalam strategi mencari jurnal framework yang digunakan adalah PICOT. Sumber data yang digunakan diambil dari database e-resources Perpusnas, PubMed dan Google Scholar kemudian diseleksi dengan menggunakan flow diagram PRISMA sehingga menghasilkan sembilan artikel. Setiap artikel telah dijabarkan dan dikritisi dalam bentuk tabel matriks menggunakan simplified approach method. Hasil penelitian ditemukan tiga tema yaitu kualitas hidup pasien PGK yang menjalankan CAPD baik, kualitas hidup pasien PGK yang menjalankan CAPD lebih baik dibandingkan dengan pasien yang menjalankan hemodialisis, dan kualitas hidup pasien PGK yang menjalankan CAPD dengan telenursing mengalami peningkatan. Telenursing dapat mempermudah akses pasien dalam mencari pelayanan kesehatan dan menambah efektivitas waktu pasien, sehingga kualitas hidup pasien dapat meningkat.